Development of a Dynamic Goniometer with an Incremental Encoder (2006)
Angle dynamic measurements of body joints have become an important parameter to know for sportsmen, physicians and analysts of rehabilitation processes. The development of devices that allows those measurements turns out to be a hard work for biomedical engineers because during the acquisition process the mechanical system usually affects the natural joints movements. Digital goniometers have been constructed using different electronic principles, especially using resistance variations in potentiometers. In this paper we propose the construction of a dynamic goniometer with an incremental encoder using a mechanical transmission between a hinge and a pulley connected to an optical disk. The rotation is detected with an infrared led and a phototransistor. Calculations are done through a microcontroller and finally shown in real time using a liquid crystal display (LCD).